Experimental studies of natural oscillations of the Earth in Antarctica and Ukraine in electromagnetic radiation - Bogdanov, Yu. A. (Geofizicheskiy Zhurnal, 2011)
Using a systemic approach to identifying hidden periodicities through the use of mathematical tools, including both spectral analysis and wavelet transform - the transformation of time series, the frequency variations of electromagnetic activity (EMA) of the Earth in Antarctica and Ukraine, with periods of time and daily ranges have been established. The structure of the vibration spectrum, the existence of stable oscillations, and grouping them on the frequency axis, the range of frequencies at which the Earth EMA occurs most frequently have been determined.